Rituximab chimeric anti-CD20 monoclonal antibody therapy for relapsed indolent lymphoma: half of patients respond to a four-dose treatment program. - McLaughlin, Peter; Grillo-López, A. J.; Link, B. K.; Levy, R.; Czuczman, M. S.; Williams, M. E.; Heyman, M. R.; Bence-Bruckler, I.; White, C. A.; Cabanillas, F.; Jain, V.; Ho, Anthony Dick; et al. (Journal of clinical oncology, 1998)
Purpose - The CD20 antigen is expressed on more than 90% of B-cell lymphomas. It is appealing for targeted therapy, because it does not shed or modulate. A chimeric monoclonal antibody more effectively mediates host effector functions and is itself less immunogenic than are murine antibodies. - Patients and Methods - This was a multiinstitutional trial of the chimeric anti-CD20 antibody, IDEC-C2B8. Patients with relapsed low grade or follicular lymphoma received an outpatient treatment course of IDEC-C2B8 375 mg/m2 intravenously weekly for four doses. - Results - From 31 centers, 166 patients were entered. Of this intent-to-treat group, 48% responded. With a median follow-up duration of 11.8 months, the projected median time to progression for responders is 13.0 months. Serum antibody levels were sustained longer after the fourth infusion than after the first, and were higher in responders and in patients with lower tumor burden. The majority of adverse events occurred during the first infusion and were grade 1 or 2; fever and chills were the most common events. Only 12% of patients had grade 3 and 3% grade 4 toxicities. A human antichimeric antibody was detected in only one patient. - Conclusion - The response rate of 48% with IDEC-C2B8 is comparable to results with single-agent cytotoxic chemotherapy. Toxicity was mild. Attention needs to be paid to the rate of antibody infusion, with titration according to toxicity. Further investigation of this agent is warranted, including its use in conjunction with standard chemotherapy.
Gesehen am 03.11.2025